2017
DOI: 10.4172/2155-6148.1000763
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Postgraduates Following Implementation of a Focus Assessed Transthoracic Echocardiography (FATE) Training Course-A Pilot Study

Abstract: At our institution, implementation of a formal training course in Basic Focus Assessed Transthoracic Echocardiography (FATE) was associated with an improvement in anesthesia trainees’ ability to obtain transthoracic echocardiography (TTE) images. Total image acquisition scores improved by a median (Q1, Q3) 9.1 (2.9,14.7) percentage points from pre-to post-hands-on FATE course (n=20; p=0.001). Participants who returned for a subsequent assessment 5 months following the course demonstrated a median (Q1, Q3) 18.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Uma história abrangente e exame físico continuam a ser a base da avaliação, assim como o uso da ecocardiografia no período perioperatório entre os anestesistas 59 . Nos últimos anos, a ecocardiografia transtorácica pré-operatória está mais disponível para os anestesistas 60 . O exame não é invasivo e pode ser concluído em 10 minutos em ambiente ambulatorial.…”
Section: Sopros Cardíacosunclassified
“…Uma história abrangente e exame físico continuam a ser a base da avaliação, assim como o uso da ecocardiografia no período perioperatório entre os anestesistas 59 . Nos últimos anos, a ecocardiografia transtorácica pré-operatória está mais disponível para os anestesistas 60 . O exame não é invasivo e pode ser concluído em 10 minutos em ambiente ambulatorial.…”
Section: Sopros Cardíacosunclassified
“…In a patient presenting with an otherwise asymptomatic cardiac murmur, although it would be useful to have transthoracic echocardiography to exclude cardiac pathology, such expertise may not always be readily accessible. Fortunately, training in, and utilisation of, pre‐operative focused transthoracic echocardiography is becoming more available to anaesthetists . The examination is non‐invasive and can be completed within 10 min in an outpatient setting.…”
Section: Cardiac Murmursmentioning
confidence: 99%
“…The assessment of an anesthesia run peri-FOCUS service showed a significant alteration in the management of most patients regarding the guidance of fluid and vasoactive drugs administration and interventional percutaneous cardiac procedures 14 . Additionally, studies have shown that the implementation of training courses resulted in quick and effective training for residents 15,16 and that medical students who complete formal training courses perceive point-of-care ultrasound training as beneficial 17 .…”
Section: Introductionmentioning
confidence: 99%